Predictive Factors for the Need of Tracheostomy in Patients With Large Vessel Occlusion Stroke Being Treated With Mechanical Thrombectomy - Maier, Ilko L.; Schramm, Katarina; Bähr, Mathias; Behme, Daniel; Psychogios, Marios-Nikos; Liman, Jan (Frontiers in Neurology, 2021)
Background: Patients with large vessel occlusion stroke (LVOS) eligible for mechanical thrombectomy (MT) are at risk for stroke- and non-stroke related complications resulting in the need for tracheostomy (TS). Risk factors for TS have not yet been systematically investigated in this subgroup of stroke patients. Methods: Prospectively derived data from patients with LVOS and MT being treated in a large, academic neurological ICU (neuro-ICU) between 2014 and 2019 were analyzed in this single center study. Predictive value of peri- and postinterventional factors, stroke imaging and pre-stroke medical history were investigated for their potential to predict tracheostomy during ICU-stay using logistic regression models. Results: From 635 LVOS-patients treated with MT, 40 (6.3%) underwent tracheostomy during their neuro-ICU stay. Patients receiving tracheostomy were younger (71 (62-75) vs. 77 (66-83), p<0.001), had a higher National Institute of Health Stroke Scale (NIHSS) at baseline (18 (15-20) vs. 15 (10-19), p=0.009) as well as higher rates of hospital acquired pneumonia (HAP) (39 (97.5%) vs 224 (37.6%), p<0.001), failed extubation (15 (37.5%) vs 19 (3.2%), p<0.001), sepsis (11 (27.5%) vs. 16 (2.7%), p<0.001), symptomatic intracerebral hemorrhage (5 (12.5%) vs. 22 (3.9%), p=0.026) and decompressive hemicraniectomy (DH) (19 (51.4%) vs. 21 (3.8%), p<0.001). In multivariate logistic regression analysis, HAP (OR 21.26 (CI, 2.76-163.56), p=0.003), Sepsis (OR 5.39 (1.71-16.91), p=0.004), failed extubation (OR 8.41 (3.09-22.93), p<0.001) and DH (OR 9.94 (3.92-25.21), p<0.001) remained as strongest predictors for TS. Patients with longer periods from admission to TS had longer ICU length of stay (r=0.384, p=0.030). There was no association between the time from admission to TS and clinical outcome (NIHSS at discharge: r=0.125, p=0.461; mRS at 90 days: r=-0.179, p=0.403). Conclusions: Patients with LVOS undergoing MT are at high risk to require TS if extubation after the intervention fails, DH is needed, and severe infectious complications occur in the acute phase after ischemic stroke. These factors are likely to be useful for the indication and timing of TS to reduce overall sedation and shorten ICU length of stay.